Efektivitas Penerapan Metode Team Assisted Individualization pada Mata Pelajaran Instalasi Penerangan Listrik - Abdul Latif; Elfizon Elfizon (Jurnal Pendidikan Teknik Elektro, 2023)
This study aims to determine the effectiveness of applying the Team Assisted Individualization method as a learning method in the class XII TITIL electric lighting installation subject at SMKN 5 Padang. In the learning process of the Electric Lighting Installation subject, the method used is still monotonous and does not increase students' interest in learning so that students' understanding of the learning material is very minimal. The Team Assisted Individualization learning method is suitable for this subject because through the application of the Team Assisted Individualization Method, students with various characteristics can be better accommodated. They can gain a deeper understanding, improve social and collaborative skills, and get personalized support tailored to their needs. This study used a quantitative approach with the one group pretest-posttest design method. The object of this research is Team Assisted Individualization and the effectiveness of its application to learning outcomes in the Electrical Lighting Installation subject. The subjects in this study were students of class XII TITL 2 at SMKN 5 Padang. The research instrument used was in the form of pretest and posttest questions in the form of objectives. Based on the average posttest score, it is in the high category. Therefore the application of Team Assisted Individualization as a learning method in the subject of electric lighting installation is said to be effective because the classical completeness score and effect size are in the high category.